Comparison of the Effectiveness of Conventional PjBL and Green Chemistry Integrated PjBL on Learning Outcomes and 21st Century Skills: SLR - Yunus, Muhammad; Islawati, Islawati (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to compare the effectiveness of conventional Project-Based Learning (PjBL) and Green Chemistry–integrated PjBL in improving learning outcomes and 21st-century skills in chemistry education. The study employed a Systematic Literature Review (SLR) approach by synthesizing findings from 17 national and international scholarly articles relevant to the research focus. The SLR process followed structured stages, including identification, selection, data extraction, and narrative synthesis. The variables analyzed included cognitive learning outcomes, 21st-century skills (Higher Order Thinking Skills, creativity, collaboration, and communication), learning engagement, environmental literacy, and project product quality. The results of the SLR indicate that both conventional PjBL and Green Chemistry–integrated PjBL are consistently reported to enhance learning outcomes and 21st-century skills compared to traditional instructional approaches. However, Green Chemistry–integrated PjBL demonstrates a broader range of learning impacts. In addition to improving academic achievement and 21st-century skills, this approach is reported to foster environmental literacy, understanding of Green Chemistry principles, student engagement, and the development of sustainability-oriented project products. These findings suggest that integrating Green Chemistry provides substantial added value to the implementation of PjBL in chemistry learning. This study concludes that Green Chemistry–integrated PjBL offers a more comprehensive pedagogical approach than conventional PjBL in supporting 21st-century chemistry education and Education for Sustainable Development. The findings are expected to serve as both a conceptual and practical reference for educators, researchers, and policymakers in designing project-based chemistry learning that emphasizes sustainability